ترا با هلوصأ و هقفلالةغل - Nurlaila, Nurlaila (Faculty of Shariah of State Institute for Islamic Studies Batusangkar, Indonesia, 2012)
Arabic language has close relationship with the fiqh (Islamic jurisprudence) and ushul fiqh (source methodology), because both of the sciences are derived from al-Quran and al-Hadith. Ulama make it as one of the ultimate requirements for those who wish to explore fiqh and ushul fiqh, because there are many differences of syar'i laws as a result of language problems. So that, understanding of arabic is compulsory for those who want to understand the laws of Allah.